2018
DOI: 10.21205/deufmd.2018205820
|View full text |Cite
|
Sign up to set email alerts
|

A Prospect on Integration of Solar Technology to Modern Greenhouses

Abstract: The demand for food products is increasing with the growing world population day by day. Given the environmental and land deterioration, agricultural requirement cannot be supply with conventional agriculture. At this point modern greenhouses are attractive alternatives. The high energy consumption of greenhouse systems is a major obstacle to sustainable production. With integration of solar technology to modern greenhouses is aimed to reduce dependence on fossil fuels and expanding the greenhouse in places wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The high temperature of the liquid in CSP causes a heat engine to work. The main applications of CSP are (i) water heating for hostel 4 , (ii) greenhouse plants 5 , and (iii) biogas production 6 . Furthermore, CSP systems are effective in storing energy using thermal energy storage technologies (TES).…”
Section: Introductionmentioning
confidence: 99%
“…The high temperature of the liquid in CSP causes a heat engine to work. The main applications of CSP are (i) water heating for hostel 4 , (ii) greenhouse plants 5 , and (iii) biogas production 6 . Furthermore, CSP systems are effective in storing energy using thermal energy storage technologies (TES).…”
Section: Introductionmentioning
confidence: 99%
“…Control of the growth medium in light, water, temperature, relative humidity, CO2 concentration, and ventilation provides optimal growing conditions for plants while improving crop yield and quality in greenhouse plant production. Many interrelated parameters can affect the environmental parameters in greenhouses, such as the size and location of the greenhouses, the type of cover material, the heat storage method, the amount and quality of the materials used, the type of cultivation, and the desired day and night temperature [1].…”
Section: Introductionmentioning
confidence: 99%
“…It would also be profitable in the future if the prices of solar-PVs decreases and the cost of electricity increases. Kocar et al, 2018 examined the integration of solar technology in modern greenhouses. The authors reported that solar-PV systems can generate the electricity required in the greenhouses which could be 20-30% of their total energy demand.…”
Section: Introductionmentioning
confidence: 99%